Refractive errors in infancy predict reduced performance on the movement assessment battery for children at 3 1/2 and 5 1/2 years. - Atkinson, J; Nardini, M; Anker, S; Braddick, O; Hughes, C; Rae, S (2005)
We have previously reported that significant hyperopia at 9 months predicts mild deficits on visuocognitive and visuomotor measures between 2 years and 5 years 6 months. Here we compare the motor skills of children who had been hyperopic in infancy (hyperopic group) with those who had been emmetropic (control group), using the Movement Assessment Battery for Children (Movement ABC). Children were tested at 3 years 6 months (hyperopic group: 47 males, 63 females, mean age 3 y 7 mo, SD 1.6 mo; control group: 61 males, 70 females, mean age 3 y 7 mo, SD 1.2 mo) and at 5 years 6 months (hyperopic group: 43 males, 56 females, mean age 5 y 4 mo, SD 1.7 mo; control group: 51 males, 62 females, mean age 5 y 3 mo, SD 1.6 mo). The hyperopic group performed significantly worse at both ages, overall and on at least one test from each category of motor skill (manual dexterity, balance, and ball skills). Distributions of scores showed that these differences were not due to poor performance by a minority but to a widespread mild deficit in the hyperopic group. This study also provides the first normative data on the Movement ABC for children below 4 years of age, and shows that it provides a useful measure of motor development at this young age.